THE EFFECT OF COOPERATIVE LEARNING MODEL THINK PAIR SHARE TYPE ON INTEGRATED SCIENCE LEARNING OUTCOMES CHARACTER - Khoiria Triana Sari; Irwan Baadilla (Physics Education Study Program, Faculty of Education and Teacher Training, UNSIQ, 2024)
This study describes the effect resulting from using cooperative learning model think pair share type of learning outcomes Science Class V integrated by the character. The purpose of this study was to determine the influence on the learning outcomes of Science Class V students caused by the use of cooperative learning model type think pair share. This type of research is a True experiment with Pretest-Postest Control Design. The population in this study are students which consists of 3 classes, namely VA, VB, and VC classes. Sampling technique in this study using Probabilty Sampling technique with Simple Random Sampling technique. After random shuffle obtained samples of 2 classes, namely the control class consists of 30 students, and experimental class consists of 29 students. This research activity by providing experimental treatment to the experimental class, while the control class was not given treatment. This study obtained the results of pretest and postest testing of students. Each obtained the pretest results of the control class is = 50.1 while the experimental class is = 49.78. After the experimental class was given treatment with think pair share type learning model and the control class was not given treatment, then the postest results of the control class were = 56.23 while the experimental class was = 79.37. Based on the results of hypothesis testing with t-test using SPSS 22.0 program obtained the results of GIS (2-tailed) is 0.000. Referring to the result Sig (2-tailed) value 0.000 < 0.05 then Ho rejected and Ha accepted. This means that in this study there is a significant difference between the learning outcomes of experimental class students and control class students